2018
DOI: 10.1016/j.jaci.2017.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators mediate airway smooth muscle contraction through a G protein-coupled receptor–transmembrane protein 16A–voltage-dependent Ca2+ channel axis and contribute to bronchial hyperresponsiveness in asthma

Abstract: A G protein-coupled receptor-TMEM16A-voltage-dependent Ca channel axis contributes to inflammatory mediator-induced ASM contraction and synergistically activated TMEM16A by allergic inflammatory mediators with cholinergic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Pharmacological activation of TMEM16A is thought to compensate for the absent CFTR-dependent Cl − secretion in CF, and therefore may represent a CFTR mutation-agnostic therapy [10]. Other studies found a role of TMEM16A for ASM contraction [6,9,11]. Such a role of TMEM16A is particularly evident under inflammatory conditions like asthma, when TMEM16A is strongly upregulated in the ASM.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological activation of TMEM16A is thought to compensate for the absent CFTR-dependent Cl − secretion in CF, and therefore may represent a CFTR mutation-agnostic therapy [10]. Other studies found a role of TMEM16A for ASM contraction [6,9,11]. Such a role of TMEM16A is particularly evident under inflammatory conditions like asthma, when TMEM16A is strongly upregulated in the ASM.…”
Section: Introductionmentioning
confidence: 99%
“…S3). Up-regulated TMEM16A in ASM strongly supports bronchoconstriction (8,26,42). Thus, blockade of TMEM16A will inhibit release of mucus and cytokines and will induce bronchodilation, which should be all beneficial in inflammatory airway disease (8,43).…”
mentioning
confidence: 98%
“…Activation of this channel causes membrane depolarization with resultant activation of L-type Ca 2ϩ channels (11). Moreover, transgenic mice lacking TMEM16A showed grossly reduced responses to 5-HT and U46619 although their responses to muscarinic stimulation was similar to wild-type mice (46). This suggests that certain inflammatory mediators involved in ASMC contraction require membrane depolarization.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are new developments, which suggest that it is premature to disregard a role for membrane potential-dependent regulation. Recently, it has been shown that the molecular identity of the Ca 2ϩ -activated Cl Ϫ channel in human and mice ASMC is TMEM16A (11,46,49). Activation of this channel causes membrane depolarization with resultant activation of L-type Ca 2ϩ channels (11).…”
Section: Introductionmentioning
confidence: 99%